2014
DOI: 10.1123/pes.2012-0207
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Social Support on Youth Physical Activity Behavior

Abstract: Social support (SS) from parents and peers are key reinforcing factors in the Youth Physical Activity Promotion (YPAP) model. This study aims to identify the relative contribution of parental and peer SS on youth participation in moderate to vigorous physical activity (MVPA). Participants included 203 high school students (n = 125 girls; mean age 14.99 ± 1.55 years). MVPA was assessed by accelerometry. SS influences were evaluated using a well-established scale. Structural equation modeling measured (AMOS, Ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 44 publications
8
39
0
7
Order By: Relevance
“…PALAVRAS-CHAVE: lazer; família; atividade física cher, Hirasing, Seidell & Renders, 2014;Silva, Lott, Mota & Welk, 2014).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…PALAVRAS-CHAVE: lazer; família; atividade física cher, Hirasing, Seidell & Renders, 2014;Silva, Lott, Mota & Welk, 2014).…”
Section: Introductionunclassified
“…Estas controversias científicas, resaltan la necesidad de seguir profundizando en investigaciones que contemplen a los progenitores, en cualquier intento por entender y potenciar las experiencias físico-deportivas de los adolescentes. & Renders, 2014;Silva, Lott, Mota & Welk, 2014).…”
Section: Introductionunclassified
“…Estos resultados concuerdan con los reportados en estudios anteriores (5,13). Por lo que, a pesar de las ligera diferencias en los valores β, superiores para el apoyo de los amigos, no podemos afirmar que en nuestra muestra este resulte significativamente más relevante que el apoyo paterno, como sugirieron Prado y cols.…”
Section: Discussionunclassified
“…Research studies have supported the relevance of family models in the establishment of drinking patterns or eating habits (Birch & Fisher, 1998;Nansel et al, 2013;Nicklas et al, 2001;Schmidt, Morrongiello, & Colwell, 2014;White et al, 2000). Peers also serve as important models influencing health behaviors such as alcohol consumption or physical activity (Sancho et al, 2011;Silva et al, 2014).…”
Section: Pbt Components: Perceived Environmental Variablesmentioning
confidence: 99%
“…Certainly, the consideration of personal and environmental variables separately constitutes a major limitation to the proper understanding of the overall context in which health behaviors are established. Moreover, research has shown that although separately considered in studies, both personal and environmental variables are involved as predictors of health behavior (Cairney, Kwan, Veldhuizen, & Faulkner, 2014;Silva, Lott, Mota, & Welk, 2014). Another argument along these lines is the repeatedly found relationship between the several health behaviors themselves (i.e., individuals engaged in physical activity also have a healthy diet; conversely, smoking and drinking also go together); hence, it might be expected that they also have common personal or environmental predictors (although the relevance of the specific predictors might vary on the specific behavior; for example, Kwan, Cairney, Faulkner, & Pullenayegum, 2012).…”
Section: Health Behaviors and The Problem-behavior Theory (Pbt)mentioning
confidence: 99%